Assessment of a novel Ehlers-Danlos syndromes disability index - Chai, Stephen; Roney, Patricia; Fagan, John; Rosario, Emily Rose (Frontiers in Rehabilitation Sciences, 2024)
The Ehlers-Danlos syndromes (EDS) are a group of inherited connective tissue disorders characterized by disruptions in collagen synthesis and processing. These disorders lead to various symptoms, including hypermobility, musculoskeletal conditions, and chronic pain that can significantly limit patients' daily living. In the absence of a curative treatment, an EDS specific disability index that tracks changes in patient-reported outcomes can facilitate the investigation of new treatment options and enhance the quality of life for EDS patients.An EDS-specific disability index was created using survey data and input from clinicians. A total of 222 EDS patients in a multidisciplinary clinical program completed the index during their initial visit. Exploratory and confirmatory factor analyses were conducted to determine the index's factor solution and assess its goodness-of-fit. Paired t-tests were performed with follow-up visit data collected over the course of one year.The exploratory and confirmatory factor analyses indicated a two-factor solution, accounting for 42.40% of the variance. The index demonstrated adequate fit to the data, supported by Tucker and Lewis's index (0.85) and root mean square error of approximation (0.1). Data from follow-up visits showed significant improvement in three symptom related variables and one function related variable in addition to the total score and the symptom subscale score when compared to the initial visit.The development of an EDS-specific disability index is a crucial step in creating a clinical tool that enables healthcare professionals to gain a deeper understanding of the impact EDS has on patients' lives and potentially identify new therapeutic interventions.